ENT 300 : Empower Cooking Enterprise / Lily Azniza Azlan ... [et al.] - Azlan, Lily Azniza; Mohamad Salleh, Nur Anisa Syamsyida; Shahrizan, Nur Syafiqah; Nor Azman, Nurin Adlina (2021)
In the year 2022, Empower Cooking Enterprise will be established. EasyPaste is a superb blend of components that contains fresh ingredients that our company offers. EasyPaste is made up of seven different cooking ingredients. Sales will be conducted both in reality and digitally via the Shopee platform. We want to offer our product to family members, adults, and students. To set ourselves apart from our competitors, we offer complimentary recipe books with 101 different dishes made with our products to all our valued customers in order to assist them with another menu on their cook list. Based on the size of our defined market area, our sales projections for the first year are RM607,00000. We expect the growth in sales rate will add 5% per year for the first three years. For cash flow, in the first year , the cash inflow is two times the cash outflow. However, for the second year, the cash inflow will be less stimulating due to no capital cash and any loan purchase. Despite that, for the third year and above, the cash inflow gets exciting due to the growth of sales mentioned earlier. Furthermore, for the first year and above, cash outflow maintains an increasing 5% year by year. The expected return on investment in the first year is 33.56%. We are seeking capital of around RM100,000.00 to finance our first-year growth. All partnership has0020invested a total of RM47,534.47. Loan and hire purchase are expected to acquire RM 58,781.24. All capital is needed to purchase fixed assets and buy all approximate expenditures from all managers and other expenditures like a deposit of rent and utilities and, foremost, the grand opening of our business. Empower Cooking Enterprise company is a form of business based on partnership. The form of the partnership was formed on 4th July 2021. As a result, the principal owner of this company is Ms Lily Azniza Binti Azlan, who also conducts as a general manager. Furthermore, there are three key personnel running the position of marketing and administration manager, an operational manager, and a financial manager. The location of our business is a strategic place where Subang Jaya is surrounded by educational institutions and residential areas. Therefore, our target customers will easily notice our existence. Furthermore, we took the opportunity to market our product if our close institutional held an open entrepreneurship day. There, we provide two different counters, where one counter is our blended product, Easypaste and the next counter is the ingredient that has not been blended yet. Many people are interested and began to get recognized with our product because it was found that in not more than 7 minutes, the food is ready.